Clinical Efficacy and Therapeutic Effectiveness of Oseltamivir in Pediatric Influenza Treatment: A Systematic Review - Dr. Krishna Priya Kanteti (Asian Journal of Pharmaceutics (AJP), 2025)
Influenza viruses cause significant morbidity and mortality worldwide each year. Diagnosing influenza based on clinical symptoms is challenging and requires laboratory confirmation for a precise diagnosis. Oseltamivir is fundamental in managing influenza; however, its effectiveness in children remains under scrutiny due to resistance. This systematic review assessed the clinical effectiveness of oseltamivir in treating children with influenza. The review included five studies that assessed the effectiveness of oseltamivir in treating influenza in children and adults across different settings. Studies have shown that oseltamivir decreases illness duration when administered early, and its combination with clarithromycin and naproxen reduces fever duration and hospital stay. Peramivir showed slightly faster fever reduction than oseltamivir, though clinical outcomes remained similar. Shorter courses of oseltamivir prophylaxis may be equally effective, potentially reducing costs. Adding oseltamivir to standard care is cost-effective, particularly in older adults with health conditions. This review confirms the limited effectiveness of oseltamivir in reducing flu symptoms in children when administered promptly, with potential benefits from combination therapy in severe pediatric cases.